2008
DOI: 10.4049/jimmunol.180.8.5283
|View full text |Cite
|
Sign up to set email alerts
|

Aging Down-Regulates the Transcription Factor E2A, Activation-Induced Cytidine Deaminase, and Ig Class Switch in Human B Cells

Abstract: Elderly humans have compromised humoral and cellular immune responses, which lead to reduced protection to infectious agents and to vaccines. Currently, available vaccines suboptimally protect the elderly population. The capacity to class switch the Ig H chain is critical to the effectiveness of humoral immune responses in mice and humans. We have previously shown in mice that the E2A-encoded transcription factor E47, which regulates many B cell functions, is down-regulated in old splenic B cells. This leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
262
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(296 citation statements)
references
References 48 publications
23
262
3
3
Order By: Relevance
“…Although the total numbers of mature B cells decrease with age (reviewed in Frasca et al 2011), conflicting reports on the ratio of naïve and memory cells exists (Kolar et al 2006;Caraux et al 2010;Bulati et al 2011;Frasca et al 2011). Furthermore, a decrease in classswitched B cells and decrease in affinity antibodies has been observed in the elderly (Frasca et al 2008). The decrease in humoral protection links B cells, similar to T cells, with immunosenescence (Bulati et al 2011;Frasca et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the total numbers of mature B cells decrease with age (reviewed in Frasca et al 2011), conflicting reports on the ratio of naïve and memory cells exists (Kolar et al 2006;Caraux et al 2010;Bulati et al 2011;Frasca et al 2011). Furthermore, a decrease in classswitched B cells and decrease in affinity antibodies has been observed in the elderly (Frasca et al 2008). The decrease in humoral protection links B cells, similar to T cells, with immunosenescence (Bulati et al 2011;Frasca et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear if the effect of CMV infection on Ig class-switch is truly CD4 independent, or if CMV induces a subtle change in the function of CD4 T-cells, which could not be measured by our assay. Alternatively, CMV may impair B-cell responses by disrupting the lymph-node architecture and thus the signaling network that is necessary for the germinal center reaction, or by direct effects on the B-cell compartment, for instance by dysregulating TNFα signaling (Frasca et al, 2012) or by affecting E47 or activation-induced cytidine deaminase, similarly to effects observed in aging mice (Frasca et al, 2008;Frasca et al, 2004). These important questions may be addressed in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, innate immunity seems to be better preserved, while more severe agedependent changes occur in the adaptive immune system (Franceschi et al 2000b). There are clear changes in B cell generation and repertoire, and as a consequence of this and changes in the T cells, elderly people show defective humoral immunity (Cancro et al 2009;Bulati Fig. (Pawelec et al 2005;Shi et al 2005;Frasca et al 2008;Veneri et al 2009;, and in previous papers, we (Colonna-Romano et al 2009) and others (Gupta et al 2005) have demonstrated that the percentage of naïve B cells are significantly reduced in aged individuals. However, this is still a somewhat controversial finding as some authors reported an increase, a decrease, or no changes in the naïve/memory B cell compartments, as we have reviewed .…”
Section: Discussionmentioning
confidence: 99%
“…The early progenitors of B lymphocytes develop into pro-, pre-, and immature B cells (LeBien and Tedder 2008) that, after they are controlled for autoreactivity (Carsetti et al 1995;Palanichamy et al 2009), leave the bone marrow and enter the blood as transitional B cells (Allman et al 1993;Chung et al 2003;Mauri and Ehrestein 2008). In humans, peripheral blood naïve and memory B cells have been described on the basis of the differential expression of IgD and CD27 (Anolik et al 2004;Shi et al 2005;Wei et al 2007;Frasca et al 2008) (Fecteau et al 2006;Colonna-Romano et al 2009). …”
Section: Introductionmentioning
confidence: 99%